The role of nonlinear pedagogy in supporting the design of modified games in junior sports - Chow, J. Y.; Komar, J.; Seifert, L. (Frontiers in Psychology, 2021)
Nonlinear Pedagogy has been advocated as an approach that views acquisition of movement skills with a strong emphasis on exploratory behaviors and the development of individualized movement skills. Underpinned by Ecological Dynamics, Nonlinear Pedagogy provides key ideas on design principles to support a teaching and learning approach that accounts for dynamic interactions among constraints in the evolution of movement behaviors. In the context of junior sports, the manipulation of task constraints is central to how games can be re-designed for children to play that are age and body appropriate so that the games can still capture the key elements of representativeness as compared to the adult form of the game. Importantly, these games offer suitable affordances that promote sensible play that could be transferable to other contexts. In this paper, we provide an in-depth discussion on how Nonlinear Pedagogy is relevant in supporting the design and development of modified games in the context of junior sports. Practical implications are also provided to share how games can be modified for meaningful play to emerge.